St Barnabas Chapel: "No Rival in that Hemisphere". Issue 3 (2nd September 2018) - Montana, Andrew
ABSTRACT: St Barnabas chapel on Norfolk Island, Australia, completed between 1880 and 1910, is an aggregate of architectural planning, structural detail, and interior ornamentation. Incorporating the Arts and Crafts philosophy of the unity of the arts, the cruciform chapel designed in the 1870s was built in memory of the first Anglican Bishop of Melanesia, John Coleridge Patteson, who was killed on the island of Nupaku near then Santa Cruz in 1871 after being mistaken for a blackbirder in search of labour for the Queensland and Fijian sugar and cotton plantations. The chapel's interior unites the work of English architect Thomas Graham Jackson, once a pupil of George Gilbert Scott, with the work of New Zealanders, Melanesian mission clergy, and young Melanesian scholars, and envelops stained glass windows by Edward Burne-Jones from Morris and Co., London. Not least, it blends modern, later nineteenth-century English design with Norfolk Island, New Zealand, and Tasmanian materials, and Islander and New Zealand ornamental patterns. Presenting nuanced cultural perspectives, this article uses archival sources and illuminates the frequently fraught circumstances behind the building of St Barnabas chapel. Further, it reveals the significant female patronage to achieve in form Bishop Patteson's prescient vision for the chapel's interior.